A case study of sports facilities in relation to the effectiveness of cheerleading training - Vivar, Dana C. (College of Home Economica, University of the Philippines Diliman, 2023)
In the Philippines, there are no interior design standards available for cheerleading training facilities. As competitive cheerleading becomes recognized as a sport by the International Olympic Committee and advances in the country, interior design standards are needed to have an effective training space for athletes and coaches. The study determines the relationship of the design of a selected sports training facility to the effectiveness of cheerleading training. It is descriptive in nature and uses qualitative and quantitative data and utilizes a purposive sampling method to select participants. The 30 respondents were collegiate athletes and coaches divided into three categories - flyers, bases, and coaches - to give the researcher different perspectives on their view of their training facility. The study used three data gathering instruments - survey questionnaire, observation checklist, and table for comparison - in order to assess the facility and compare the existing space components with the available literature. Results of the study showed that the selected sports training facility have issues in terms of specific spatial components and its non-conformity to the National Building Code of the Philippines (Presidential Decree No. 1096) and the Fire Code of the Philippines (Republic Act No. 9514). This negatively affects the performance of the selected collegiate cheerleading team, how the athletes and coaches conduct their training, and the safety and security of the users in the space. A guideline of changes was made in order to address these issues and for the space to be conducive for collegiate cheerleading training in the Philippines.